An economist, an engineer or a manager-engineer? - Znamierowska, Teresa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2007)
This paper aims at concisely presenting some activities that have been undertaken in 1996 and resulted in a new interdisciplinary field of study labelled as production management and engineering. In order to understand the validation of those activities, it is necessary to look back and to review
Argumenta Oeconomica, 2007, No 1-2 (19), s. 237-246
Keywords: production management and engineering; interdisciplinary field o f study; higher education; engineering management; management and marketing; the working group